FAKCTORS RELATED WITH EXISTENCE OF MOSQUITO REPELLENT AEDES AEGYPTI IN WORK AREA HARAPAN RAYA PUBLIC HEALTH CENTER IN 2020: FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEBERADAAN JENTIK NYAMUK AEDES AEGYPTI DI WILAYAH KERJA PUSKESMAS HARAPAN RAYA TAHUN 2020 - marni juliastari; Herlina Susmaneli; Sri Wardani; Ikhtiaruddin Ikhtiaruddin; Christine Vita Gloria Purba (STIKes Hang Tuah Pekanbaru, 2021)
The cause of Dengue Hemorrhagic Fever is the bite of the mosquito Aedes Aegypty which enters the human blood circulation. It was found that the percentage of the House Index was 93.3% of the mosquito larvae in the houses of residents in the working area of ​​the Harapan Raya Health Center. The Objective is to determine the factors associated with the presence of mosquito larvae Aedes Aegypti. This study is quantitative analytic observational with a design cross sectional. The measuring instrument uses a questionnaire through interviews, observations, and checklists. The population is 13,750 heads of house hold (KK), the total sample is 189 house holds. Technique Purposive Sampling. Data analysis usingtest Chi square. Results showed the proportion of larvae Aedes Aegypti is 58.7%. Factors related to the presence of mosquito larvae Aedes Aegypti were knowledge (P=0.001; POR=18,494 (CI=8,796-38,881), attitude (P=0.001; POR=5,000 (CI=2,608-9.587), jumantic activity (P = 0.001; POR = 4.717 (CI = 2.519-8.834), the presence of solid waste (P = 0.001; POR = 2.996 (CI = 1.632-5.498), the practice of eradicating mosquito nests (P = 0.001; POR = 136,000 (CI = 46,363- 398,935), and water reservoirs (P=0,028; POR=0,400 (CI=0,335-0,447) The conclusion of seven factors studied were: knowledge, attitudes, jumantic activity, presence of solid waste, practice of eradicating mosquito nests, and water reservoirs. significantly related to the presence of mosquito larvae Aedes Aegypti.